2008
DOI: 10.2320/matertrans.mra2008071
|View full text |Cite
|
Sign up to set email alerts
|

Non-Conductive Adhesive (NCA) Trapping Study in Chip on Glass Joints Fabricated Using Sn Bumps and NCA

Abstract: Chip-on-glass (COG) bonding using a nonconductive adhesive (NCA) and the entrapment of NCA and fillers in the COG joints were studied. Sn was used as a bump material because it has a higher propensity of plastic deformation than an Au bump. Three types of Sn bumps were fabricated, electroplated Sn bumps, reflowed Sn bumps, and coined Sn bumps. Three types of NCAs were applied during COG bonding. The reflowed bump had the least amount of trapped NCA with fillers among the bumps studied. The NCA with the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…6, the NCA-processed joints on the Si substrate exhibited large contact resistances compared with those of the ACA-bonded joints. For a chip-on-glass (COG) process using Sn bumps and NCA, a considerable amount of NCA was entrapped within an interface area of approximately 720% of the COG joint due to the surface roughness of the Sn bumps, 28) and the interface resistance R i and subsequently, the contact resistance increased with increasing amounts of entrapped NCA. In our previous work, 8) we also reported that the contact resistance of the flip-chip joints formed with NCA on a rigid Si substrate was dependent upon the degree of surface roughness of the Cu/Sn bumps.…”
Section: Resultsmentioning
confidence: 99%
“…6, the NCA-processed joints on the Si substrate exhibited large contact resistances compared with those of the ACA-bonded joints. For a chip-on-glass (COG) process using Sn bumps and NCA, a considerable amount of NCA was entrapped within an interface area of approximately 720% of the COG joint due to the surface roughness of the Sn bumps, 28) and the interface resistance R i and subsequently, the contact resistance increased with increasing amounts of entrapped NCA. In our previous work, 8) we also reported that the contact resistance of the flip-chip joints formed with NCA on a rigid Si substrate was dependent upon the degree of surface roughness of the Cu/Sn bumps.…”
Section: Resultsmentioning
confidence: 99%
“…Once the filler was trapped between Sn bumps and ITO pads, the NCA was also trapped near the filler because a gap between the fillers and Sn bump was formed, into which NCA easily flowed. 18) Additionally, as the filler was harder, more NCA and filler were trapped because harder filler was easily embedded in the soft Sn bump. As a result, NCA and The Effect of Fillers in Nonconductive Adhesive on the Reliability of Chip-on-Glass Bonding with Sn/Cu Bumpsfillers were trapped to a lesser degree in the COG joints using NCA-B compared to those using NCA-C because the silica with NCA-C is harder than the fluoropolymer with NCA-B.…”
Section: Discussionmentioning
confidence: 99%
“…As the amount of trapped NCAs increased, the contact resistance slightly increased because the contact area decreased. 18) If hard fillers were added to the NCA, it was easily embedded in the soft Sn during bonding because the Sn has a low hardness and the high plastic deformation capability. Once the filler was trapped between Sn bumps and ITO pads, the NCA was also trapped near the filler because a gap between the fillers and Sn bump was formed, into which NCA easily flowed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au is the most common bump material [11,15,16,18]. We recently developed an ultra-fine pitch COG bonding technology using NCA and Sn bumps [20][21][22][23][24][25]. This technology also has applied to COP bonding [24] and COF bonding [25].…”
Section: Introductionmentioning
confidence: 99%